Molecular, chemical and morphological evidence for hematite biogenicity at the Quaternary Cape Vani Mn-(Ba-Fe) deposit, Milos, Greece - Kilias, S.P.; Chatzitheodoridis, E.; Lyon, I. (Bulletin of the Geological Society of Greece, 2013)
Many aspects of the biotic or abiotic origin of iron-rich sedimentary rocks consisting mainly of hematite, an important indicator for exobiology, remain unresolved. Here, we use combined optical microscopy, scanning electron microscopy and energy dispersive X-ray spectrometry (SEM-EDS), Raman spectroscopy and time-of-flight secondary ion mass spectrometry (TOF-SIMS), to image the spatial distribution, and determine the composition, of potential biogenic markers (microbial microfossils, trace elements, organic ion species) in hematitemicrostromatolites and oncolite-like microstructures. These structures are identified in iron-rich material cementing a Quaternary fossil-beach conglomerate deposit in the Cape Vani area, NW Milos Island, Greece. The combined detection of morphological, chemical, and molecular organic-ion, biomarkers closely associated with possible hematite microfossils within microstromatolite laminae, strongly supports microbial mediation for their formation, and indicates that hematitic microlamination may be used as a biosignature for Fe-rich biomats on Earth and for their detection in extra-terrestrial materials. The Cape Vani hematitemicrostromatolites may contribute to growing our understanding of the function of microorganisms in the genesis of modern and ancient Fe deposits.